As metas socioeconômicas denominadas Objetivos de Desenvolvimento do Milênio da ONU: os percalços de um projeto de combate à pobreza absoluta e à exclusão social - Maria José de Rezende (Universidad Autónoma del Estado de México, 2007)
The socio economic aims established by the United Nations (ODM) have the pur pose of fighting extreme poverty, famine, inequalities, infant mortality, several diseases (AIDS, tuberculosis, ma laria), difficulty of access to basic education, environment depredation and poor countries difficulties in obtaining means of access to the market and new information as well as communication technologies. These are broad pur poses with well-de fined aims and concerned about the several spheres of social life. Many of these purposes have been fol lowed up by UNO through its various organisms such as UNICEF, UNESCO, FAO and CEPAL since the 1950s. One of the singularities concerning the current proposal of the United Nations has to be read based on a process that points to the weakening of the national State power to be ahead of the actions which aim to reach the puposes followed until 2015. It is considered then, that a visible hitch in the way of implementing the measures that aim to fight extreme in equality and the several forms of exclusion, is the way the United Nations have declared as irreversible the difficulty of the public authorities to be the agent of the implementation of these socioeconomic aims.